Pengaruh Experiential Marketingterhadap Kepuasan Pengunjung (Studi pada Pengunjung Milkindo Berka Abadi Kepanjen Malang) - Muhammad Arofi; Candra Wahyu Hidayat; Iva Nurdiana Nurfarida (Jurnal Riset Mahasiswa Manajemen, 2019)
This study aimed to find out whether Experiential Marketing opposed the Study of Visitor Satisfaction (Study on Milkindo Berka Abadi Visitors Kepanjen Malang). The independent variable in this study is Experiential Marketing which consists of (sense, feel, think, act, andrelate), while the variables obtained in this study are Visitor Satisfaction. This research was conducted in Kepanjen Regency of Malang and by using a sample of 102 perpetual Indonesian milk collectors. The sampling technique in this study is to used accidental sampling. The analysis technique used is multiple linear regression. Experiential Marketing which consists of (sense, feel, think, act, andrelate), arranged partially or simultaneously on Visitor Satisfaction.